Analysis of the Position of the Tactical Vehicle Defense Industry on the National Defense Development in a Logistics Perspective - Lomboan, Dave M.H (ARISTO, 2022)
The defense industry is part of the pillars of empowering the state's defense posture, especially in times of peace. Tactical vehicles are part of the defense industry which is an industry downstream. In this research, we analyzed the position of the tactical vehicle industry on the part of national defense empowerment. The concept of national defense explains the defense and threat spectrum. The logistics concept provides a framework analysis of the national defense empowerment and military operations. The first analysis is the industry of tactical vehicles in legal aspect is part of national defense posture. On strategic logistic levels, this industry plays a role in meeting the needs of national defense empowerment requirements in tactical vehicles. The last, tactical logistics levels play the role as the main or support power in the military operations of TNI.